Захист даних користувачів в інформаційних системах - Задерейко, Олександр Владиславович; Трофименко, Олена Григорівна; Логінова, Наталія Іванівна; Прокоп, Юлія Віталіївна; Кухаренко, Сергій Вікторович; Дика, Анастасія Іванівна (Київ : Державний науково-дослідний інститут МВС України, 2022)
У статті проведено аналіз способів збору даних з інформаційних систем користувачів, представлених пристроями комунікації, під час обміну даними з цифровим простором. Показано, що провідні світові IT-корпорації фактично монополізували цифровий ринок даних користувачів за рахунок організації процесів їх збору, зберігання та обробки. Це дозволяє формувати необхідні керуючі впливи на користувачів цифрового простору. Установлено, що DNS трафік пристрою комунікації (фіксується DNS серверами провайдера, що становить загрозу приватності користувачів. Розроблено комплекс заходів, який дозволяє організувати захист від витоків даних користувачів у інформаційних системах.

Research article analyzes the methods of data collection from users’ information systems represented by communication devices when performing data exchange with digital space. The study shows that the world’s leading IT corporations have actually monopolized the digital market of user data by organizing the processes of their collection, storage, and processing. This makes it possible to form the required control actions on users of the digital space. It has been established that the provider’s DNS servers record the DNS traffic of the communication device. This poses a threat to users privacy. We developed a set of measures to organize protection against user data leaks in information systems. Research article proposes models of software and hardware organization of users data protection from leaks in information systems. Experimental verification of the proposed models of data protection organization was carried out. The use of the proposed data protection models against leaks allowed users to increase privacy when interacting with the digital space. We experimentally established that the most effective data protection against leaks is provided by a model based on the simultaneous use of software and hardware data protection. We experimentally confirmed that with the practical implementation of simultaneous software and hardware organization of data protection, the functionality and operability of the system and application software of the communication device is preserved. The study shows that the implementation of the proposed data protection models against unauthorized leaks by the user will significantly reduce the volume of network traffic of the communication device.
Захист даних користувачів в інформаційних системах / О. В. Задерейко, О. Г. Трофименко, Ю. В. Прокоп, Н. І. Логінова, С. В. Кухаренко, А. І. Дика // Сучасна спеціальна техніка : науково-практичний журнал. - Київ : Державний науково-дослідний інститут МВС України, 2022. - № 1 (68). - С. 23-33.
Keywords: DNS запит; DNS сервер; DNS трафік; збір персональних даних; інформаційна зброя; захист персональних даних; блокування витоків даних; фільтрація з’єднань інформаційних систем; модель фільтрації; мережевого трафіку; пристрій комунікації; DNS query; DNS server; DNS traffic; personal data collection; information weapon; personal data protection; blocking data leaks; filtering connections of information systems; network traffic filtering model; communication device